Global mobility of research scientists : the economics of who goes where and why - Geuna, Aldo; Bentley, J. Scott; Rogers, Mark; Appelt, Silvia (Academic Press, 2015)
Global Mobility of Research Scientists: The Economics of Who Goes Where and Why brings together information on how the localization and mobility of academic researchers contributes to the production of knowledge. The text answers several questions, including "what characterizes nationally and internationally mobile researchers?" and "what are the individual and social implications of increased mobility of research scientists?" Eight independent, but coordinated chapters address these and other questions, drawing on a set of newly developed databases covering 30 countries, including the US, the UK, France, Germany, Italy, Japan, Russia, and China, among others. Combines theoretically sound and empirically fascinating results in one volume that has international and interdisciplinary appeal. Covers topics at the forefront of academic, business, and policy discussions Data used in the chapters available at a freely-accessible website.